When self‐prioritization crosses the senses: Crossmodal self‐prioritization demonstrated between vision and touch. - Schäfer, Sarah; Wesslein, Ann‐Katrin; Spence, Charles; Frings, Christian (British Journal of Psychology, 2021)
The investigation of self‐prioritization via a simple matching paradigm represents a new way of enhancing our knowledge about the processing of self‐relevant content and also increases our understanding of the self‐concept itself. By associating formerly neutral material with the self, and assessing the resulting prioritization of these newly formed self‐associations, conclusions can be drawn concerning the effects of self‐relevance without the burden of highly overlearned materials such as one's own name. This approach was used to gain further insights into the structure and complexity of self‐associations: a tactile pattern was associated with the self and thereafter, the prioritization of the exact same visual pattern was assessed – enabling the investigation of crossmodal self‐associations. The results demonstrate a prioritization of self‐associated material that rapidly extends beyond the borders of a sensory modality in which it was first established.